ChemInform Abstract: An Oxofluoride Catalyst Comprised of Transition Metals and a Metalloid for Application in Water Oxidation. Issue 47 (November 2015) - Svengren, Henrik; Hu, Shichao; Athanassiadis, Ioannis; Laine, Tanja M.; Johnsson, Mats
Abstract: Both single crystals and ground powder of the solid solution (Cox Ni1‐x )3 Sb4 O6 F6 exhibit catalytic activity for water oxidation, chemical resistance to wear after repeated in situ tests, and a mechanical hardness of 2.86 GPa using Vickers indentation test on single crystals.